2013
DOI: 10.2528/pier13020602
|View full text |Cite
|
Sign up to set email alerts
|

Super/Zero Scattering Characteristics of Circular SRR Arrays

Abstract: Abstract-The ability to control the scattering property of an object is important in many applications. In this paper, we propose and study the scattering characteristics of a circular array of split-ring resonators (SRRs). By calculating the scattered energy spectrum, we show that the proposed structure has a localized surface plasmon resonance like behavior, which makes it useful as a super scatterer. Furthermore, in a special case, the proposed structure exhibits transparency to the illuminated waves, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…In [1], it has been shown, that a conducting cylinder coated with a DNG (Double Negative) material made of a dielectric substrate with helical strips on its external face, achieves a larger monostatic RCS than the PEC cylinder with an equal radius. In [2], the authors propose a cylindrical structure made of SRRs (Split Ring Resonators), resulting in a very high resonant scattering object. The definition of a superscatterer first appeared in [3], where by using the transformation optics it has been shown that a coating with both anisotropic permeability and permittivity is needed for a PEC 2D cylinder to obtain a high monostatic RCS.…”
mentioning
confidence: 99%
“…In [1], it has been shown, that a conducting cylinder coated with a DNG (Double Negative) material made of a dielectric substrate with helical strips on its external face, achieves a larger monostatic RCS than the PEC cylinder with an equal radius. In [2], the authors propose a cylindrical structure made of SRRs (Split Ring Resonators), resulting in a very high resonant scattering object. The definition of a superscatterer first appeared in [3], where by using the transformation optics it has been shown that a coating with both anisotropic permeability and permittivity is needed for a PEC 2D cylinder to obtain a high monostatic RCS.…”
mentioning
confidence: 99%